2013
DOI: 10.1017/s0022381612000898
|View full text |Cite
|
Sign up to set email alerts
|

International Institutions and Civil War Prevention

Abstract: We examine the potential of highly structured intergovernmental organizations (HSIGOs) to prevent the escalation of low-level, domestic armed conflicts in member states to civil wars. A state's membership in HSIGOs alters the bargaining game between the government and rebels by increasing the costs of escalation (e.g., via sanctions) and decreasing the amount of benefits the state hoped to receive from future international cooperation. The anticipation of such consequences provides the government with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The first indicator, IO institutionalization, captures the degree of independent decisionmaking power, central monitoring, and enforcement capacity of the IGO. We source this variable from Karreth and Tir (2013), who build on earlier coding by Boehmer, Gartzke, and Nordstrom (2004) to categorize organizations into low, medium, and highly structured organizations. 85 Countries may be less likely to withdraw from highly institutionalized organizations because they include the monitoring and enforcement capabilities that can help states achieve centralization, independence, information sharing, and economies of scale, among others.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The first indicator, IO institutionalization, captures the degree of independent decisionmaking power, central monitoring, and enforcement capacity of the IGO. We source this variable from Karreth and Tir (2013), who build on earlier coding by Boehmer, Gartzke, and Nordstrom (2004) to categorize organizations into low, medium, and highly structured organizations. 85 Countries may be less likely to withdraw from highly institutionalized organizations because they include the monitoring and enforcement capabilities that can help states achieve centralization, independence, information sharing, and economies of scale, among others.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The argument that international institutions can impact the processes of domestic democratization has also been expanded to other fronts, with authors such as Greenhill (2010) reinforcing Pevehouse's findings on the capacity for democratic socialization associated with IOs, noting that they have "a surprisingly powerful influence" not only on democracy promotion, but on the diffusion of human rights norms as a whole; Karreth and Tir (2013) also suggest that IOs can prevent the escalation of armed conflict at the domestic level through the same causal mechanisms identified by Pevehouse (2002), by increasing the costs of escalation and providing safeguards for both government and rebel forces that certain rights and guarantees will be respected; and Thyne et al (2018) point out how the international posture, especially when coordinated through international institutions, not only increases the chances of a regime liberalizing itself, but also influences on the duration of coup-born regimes. Furthermore, authors Pereira, A. E. Mural Internacional, Rio de Janeiro, Vol.11, e46544, 2020.…”
Section: The Recent Debate (2010-2019)mentioning
confidence: 99%
“…The literature has consistently found that having United Nations peacekeepers deployed significantly reduces the risk of conflict recurrence (Doyle and Sambanis, 2006; Fortna and Howard, 2008; Hegre et al, 2011). Karreth and Tir (2013) look at the effect of IGOs on the escalation of civil wars, and argue that IGOs increase the cost of escalating a conflict by imposing sanctions that decrease the present and future benefits of winning a war. They find strong evidence in favor of IGOs reducing the risk of conflict escalation when focus is restricted to highly institutionalized IGOs.…”
Section: Regime Change and Intergovernmental Organizationsmentioning
confidence: 99%
“…They find strong evidence in favor of IGOs reducing the risk of conflict escalation when focus is restricted to highly institutionalized IGOs. Both Boehmer et al (2004) for the international arena and Karreth and Tir (2013) for the domestic arena argue that international organizations have the potential for altering the bargaining game between the two opposing sides, alleviating both informational asymmetries and commitment issues…”
Section: Regime Change and Intergovernmental Organizationsmentioning
confidence: 99%
See 1 more Smart Citation